2018
DOI: 10.1097/iae.0000000000001543
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Capillary Density in Patients With Birdshot Chorioretinopathy

Abstract: The decrease in visual acuity in patients with BCR is associated with retinal vascular impairment. Vessel density of the retinal capillary plexuses may be a promising imaging biomarker for BCR disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…Consistent with previous findings, the patients with Behçet's disease and VKH, both VDs, were reported to present decreased SCP and DCP compared to healthy controls (1,15). A reduction of VDs in the SCP and DCP detected by OCTA in birdshot chorioretinopathy has also been reported (23). It was also found in children with anterior uveitis that the VDs in the SCP and DCP were significantly reduced when compared with NCs, suggesting anterior segment inflammation in pediatric uveitis is associated with reduced retinal vascular density (22).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous findings, the patients with Behçet's disease and VKH, both VDs, were reported to present decreased SCP and DCP compared to healthy controls (1,15). A reduction of VDs in the SCP and DCP detected by OCTA in birdshot chorioretinopathy has also been reported (23). It was also found in children with anterior uveitis that the VDs in the SCP and DCP were significantly reduced when compared with NCs, suggesting anterior segment inflammation in pediatric uveitis is associated with reduced retinal vascular density (22).…”
Section: Discussionsupporting
confidence: 88%
“…Roberts et al reported on 37 eyes (21 patients) with BCR vs a similar number of healthy controls, and noted that the capillary density of the full retina, and both the superficial capillary plexus and deep capillary plexus were reduced in BCR compared to the healthy controls. 90 Importantly visual acuity in the BCR group was associated with a reduced capillary density, whereas FAZ area did not appear to have an effect.…”
Section: Birdshot Uveitismentioning
confidence: 82%
“…Many studies (16)(17)(18)(19) can explain the above results. Previous research has found that in patients with sellar tumors that cause compression of the optic nerve, the reasons for the visual impairment may be divided into the following three types.…”
Section: Discussionmentioning
confidence: 92%